Effect of Workplace- versus Home-Based Physical Exercise on Muscle Response to Sudden Trunk Perturbation among Healthcare Workers: A Cluster Randomized Controlled Trial. (25th October 2015) - Jakobsen, Markus D.; Sundstrup, Emil; Brandt, Mikkel; Jay, Kenneth; Aagaard, Per; Andersen, Lars L.
Abstract : Objectives . The present study investigates the effect of workplace- versus home-based physical exercise on muscle reflex response to sudden trunk perturbation among healthcare workers. Methods . Two hundred female healthcare workers (age: 42 [SD 11], BMI: 24 [SD 4], and pain intensity: 3.1 [SD 2.2] on a scale of 0–10) from 18 departments at three hospitals were randomized at the cluster level to 10 weeks of (1) workplace physical exercise (WORK) performed in groups during working hours for 5 × 10 minutes per week and up to 5 group-based coaching sessions on motivation for regular physical exercise, or (2) home-based physical exercise (HOME) performed during leisure time for 5 × 10 minutes per week. Mechanical and neuromuscular (EMG) response to randomly assigned unloading and loading trunk perturbations and questions of fear avoidance were assessed at baseline and 10-week follow-up. Results . No group by time interaction for the mechanical trunk response and EMG latency time was seen following the ten weeks (P = 0.17–0.75). However, both groups demonstrated within-group changes (P < 0.05 ) in stopping time during the loading and unloading perturbation and in stopping distance during the loading perturbation. Furthermore, EMG preactivation of the erector spinae and fear avoidance were reduced more following WORK than HOME (95% CI −2.7–−0.7 (P < 0.05 ) and −0.14 (−0.30 to 0.02) (P = 0.09 )), respectively. WORK and HOME performed 2.2 (SD: 1.1) and 1.0 (SD: 1.2) training sessions per week, respectively. Conclusions . Although training adherence was higher following WORK compared to HOME this additional training volume did not lead to significant between-group differences in the responses to sudden trunk perturbations. However, WORK led to reduced fear avoidance and reduced muscle preactivity prior to the perturbation onset, compared with HOME. This trial is registered with Clinicaltrials.gov (NCT01921764 ).